Promotion Analysis of Mooika Beauty Body Scrub Products Through Tiktokshop: Analisis Promosi Produk Body Scrub Mooika Beauty Melalui Tiktokshop - Imro'atuz Sholichah; Nur Maghfirah Aesthetika (Academia Open, 2024)
This study aims to analyze the promotion of Mooika Beauty's Body Scrub through TikTokshop, employing a qualitative research method. Data collection involved observation and documentation focused on the @moikabeautyofficial TikTokshop account. Utilizing 17 TikTokshop features, the study found optimal utilization in 15 features, with story and highlight features being underutilized. The application of the 7Ps marketing mix revealed comprehensive communication strategies. This research contributes to a deeper understanding of effective promotional practices on TikTokshop and provides insights for marketers seeking to enhance their product promotion strategies in the digital era. Highlights : TikTokshop Utilization: Examines the optimal use of TikTokshop features for promoting Mooika Beauty's Body Scrub, shedding light on effective digital marketing strategies. Qualitative Analysis: Utilizes a qualitative research method to analyze the promotional tactics employed on TikTokshop, providing in-depth insights into the dynamics of online product promotion. 7Ps Marketing Mix: Investigates the application of the 7Ps marketing mix, emphasizing the importance of a comprehensive approach in communication strategies for successful product promotion. Keywords: TikTokshop, Mooika Beauty, Body Scrub, Digital Marketing, Promotional Strategies